Earthworm effects on permanent soil seed banks in Colombian grasslands - Decaëns, Thibaud; Mariani, L; Betancourt, N.; Jiménez Jaén, J.J. (International Center for Tropical Agriculture, 2001)
The effects of Martiodrilus carimaguensis (Oligochaeta, Glossoscolecidae) on soil seed banks was investigated in a Colombian savanna and two introduced pastures. Germination and washing-sieving methods were used to compare seed density, diversity, and germination rates in earthworm casts and the surrounding soil. Large amounts of seeds were present in casts (58 to 163 seeds/100 g dry casts), which germination rates were 3 to 40 times lower than in soil, likely as a consequence of damages suffered during the gut transit. Species composition of germinable seeds was quite different in casts and soil, maybe because of selective seed ingestion by earthworms. From 1% to 13% of the total germinable soil seed bank were deposited in surface casts each year. In the savanna and one pasture, seedling species composition was closer to the vegetation in the case of casts than in the case of soil. This may indicate that ingested seeds that survive gut transit have greater chances to germinate than those of the soil seed bank. Thus, casts may be considered as a regeneration niche for plant species, and earthworm activity as a factor enhancing the expression of the soil seed bank in the standing vegetation.